Arsenophonus, an emerging clade of intracellular symbionts with a broad host distribution - Nováková, Eva; Hypsa, Václav; Moran, Nancy A (BMC microbiology, 2009)
BACKGROUND: The genus Arsenophonus is a group of symbiotic, mainly insect-associated bacteria with rapidly increasing number of records. It is known from a broad spectrum of hosts and symbiotic relationships varying from parasitic son-killers to coevolving mutualists.The present study extends the currently known diversity with 34 samples retrieved mainly from hippoboscid (Diptera: Hippoboscidae) and nycteribiid (Diptera: Nycteribiidae) hosts, and investigates phylogenetic relationships within the genus. RESULTS: The analysis of 110 Arsenophonus sequences (incl. Riesia and Phlomobacter), provides a robust monophyletic clade, characterized by unique molecular synapomorphies. On the other hand, unstable inner topology indicates that complete understanding of Arsenophonus evolution cannot be achieved with 16S rDNA. Moreover, taxonomically restricted Sampling matrices prove sensitivity of the phylogenetic signal to sampling; in some cases, Arsenophonus monophyly is disrupted by other symbiotic bacteria. Two contrasting coevolutionary patterns occur throughout the tree: parallel host-symbiont evolution and the haphazard association of the symbionts with distant hosts. A further conspicuous feature of the topology is the occurrence of monophyletic symbiont lineages associated with monophyletic groups of hosts without a co-speciation pattern. We suggest that part of this incongruence could be caused by methodological artifacts, such as intragenomic variability. CONCLUSION: The sample of currently available molecular data presents the genus Arsenophonus as one of the richest and most widespread clusters of insect symbiotic bacteria. The analysis of its phylogenetic lineages indicates a complex evolution and apparent ecological versatility with switches between entirely different life styles. Due to these properties, the genus should play an important role in the studies of evolutionary trends in insect intracellular symbionts. However, under the current practice, relying exclusively on 16S rRNA sequences, the phylogenetic analyses are sensitive to various methodological artifacts that may even lead to description of new Arsenophonus lineages as independent genera (e.g. Riesia and Phlomobacter). The resolution of the evolutionary questions encountered within the Arsenophonus clade will thus require identification of new molecular markers suitable for the low-level phylogenetics.
Keywords: RNA ribozomální 16S; bakteriální geny; symbióza; Evolution, Molecular; DNA bakterií; sekvenční seřazení; Genes, Bacterial; RNA, Ribosomal, 16S; fylogeneze; DNA, Bacterial; Symbiosis; Sequence Analysis, DNA; sekvenční analýza DNA; zvířata; Animals; Diptera; Sequence Alignment; Phylogeny; molekulární evoluce; Enterobacteriaceae